Representation of Women's Self-Image in Okky Madasari's Novels - Kartika, Aulia Cika; Efendi, Anwar (East Asian Journal of Multidisciplinary Research, 2024)
This research is a qualitative descriptive research. The subject of this study was a novel entitled Maryam, Pasung Jiwa, and Entrok by Okky Madasari. This study focused on the self-image of female characters which was studied using feminist literary criticism studies of psychoanalysis. Data obtained from reading techniques and painting techniques. The data were analyzed by qualitative descriptive analysis techniques. The validity of the data is obtained through validity and reality. The results of this study show first, the form of women's self-image in the novel Maryam, Pasung Jiwa and Entrok by Okky Madasari consists of two images. The first image is in the form of a female self-image seen from the physical. Then the second image is a psychic image consisting of independence, weakness, courage, intellectuality, love, sadness, responsibility, social spirit, and self-worth.